The Association Between Family Environment and Adolescent Alcohol Drinking Behavior: A Cross-Sectional Study of Six Chinese Cities - Chi, Ruixin; Lu, Shijun; Zhang, Na; Zhang, Man; Guo, Kaiwei; Du, Songming; Guo, Jing; Hu, Xiaoqi; Ma, Guansheng (Frontiers in Nutrition, 2022)
Objective: Adolescents’ alcohol consumption has lifetime adverse physical and mental health effects. Family environment factors have a significant influence in shaping adolescents’ beliefs and habits. We conducted the multicenter cross-sectional study aiming to investigate the association between family environment factors and adolescent drinking behavior in China. Methods: The study investigated 27,762 middle school students from Beijing, Shanghai, Guangzhou, Jinan, Chengdu, and Harbin. A logistic regression model was used to explore the association between family environmental factors and adolescent drinking behavior. Participants were asked to self-report previous experiences of drinking and getting drunk to access their drinking status. Factors of family environment related to alcohol consumption included: parents' educational level, family economic status, family composition, the number of times parents drank alcohol in the past 30 days, and parents' attitudes toward their drinking behavior. The logistic regression model was used to adjust the demographic confounders, including gender, age, city, location, and smoking status, and to explore the association between family environmental factors and adolescent alcohol drinking behaviors. Results: Compared with students whose parents prohibited drinking, students who were approved drinking were more likely to drink in this year (OR=16.544, 95%CI :15.265-17.929, P<0.001; Full adjustment: OR=13.111, 95% CI: 12.031-14.288, P<0.001), drink in this month (OR = 7.791, 95% CI: 7.077-8.565, P<0.001; Full adjustment: OR =6.010, 95% CI: 5.439-6.641, P<0.001). In addition, Low family economic status, not living with the mother, parents' ambivalent attitudes toward their children's drinking and parental drinking were risk factors for drinking among middle school students. Conclusion: The family environment , especially parents’ attitudes, is associated with students' drinking and drunken behavior. Mobilizing the power of parents may play a positive role in the effective prevention and control of adolescent drinking.